Splunk Operational Intelligence Cookbook : Over 80 recipes for transforming your data into business-critical insights using Splunk, 3rd Edition. - Mock, Derek (Packt Publishing, 2018)
This book demonstrates the power of Splunk 7.x to offer you quick solutions and strategies to bring efficient operational intelligence in your organization. Implement a wide range of tasks in recipe format to perform operations on machine data. Learn to achieve intelligent data-driven way using machine learning capabilities to explore complex data.